2006
DOI: 10.1016/j.ajog.2005.12.059
|View full text |Cite
|
Sign up to set email alerts
|

A new hypothesis about the origin of uterine fibroids based on gene expression profiling with microarrays

Abstract: This article will discuss some recent insights based on our microarray studies that have emphasized the role the extracellular matrix, transforming growth factor beta, and collagen structure in fibroid formation. These studies led to appreciation of molecular similarities between fibroids and keloids. Collectively, these observations suggest a model of fibroid development based on an abnormal response to tissue repair, resulting in disordered healing and formation of an altered extracellular matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
162
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(173 citation statements)
references
References 35 publications
10
162
0
1
Order By: Relevance
“…This hypothesis was discussed as early as the 1930s, 29 but has never been carefully tested. 12 Recent suggestions that fibroid pathogenesis mimicks abnormal wound healing, 30 and possible involvement of inflammation 31 provides impetus for trying to carefully evaluate this hypothesis.…”
Section: Methodsmentioning
confidence: 99%
“…This hypothesis was discussed as early as the 1930s, 29 but has never been carefully tested. 12 Recent suggestions that fibroid pathogenesis mimicks abnormal wound healing, 30 and possible involvement of inflammation 31 provides impetus for trying to carefully evaluate this hypothesis.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14][15][16] Our previous studies of uterine fibroids using microarrays have served to focus attention on the ECM of uterine fibroids and the similarity of fibroids to tissue remodeling and repair. 34 We noted that fibroids were composed of an ECM with altered organization of structural elements, such as collagen fibers.18 In addition, we17 and others12,15,35 have noted that fibroid express altered levels of key proteoglycans, such as dermatopontin and versican. The current study supports and extends upon the notion of altered tissue repair, because formation of a load-bearing ECM is a key step in tissue repair.…”
Section: Commentmentioning
confidence: 99%
“…Furthermore, a review of gene expression data revealed concordant changes in the genes regulating retinoid synthesis, insulin-like growth factor metabolism, transforming growth factor signaling and extracellular matrix formation (7). A larger scale gene expression analysis also contributed to a better understanding of UL (8). However, the biology of UL remains obscure.…”
Section: Introductionmentioning
confidence: 99%